The effect red betel leaves (Piper Crocatum) on vaginal discharge (Fluor Albus) in teenagers - Rachman, Sandy Nurlaela; Skania, Pratiwi Cahya; Ayustina, Selvira (Science Midwifery, 2024)
Vaginal discharge (fluor albus) is a physiological thing that can occur in teenage girls, but if it is not treated immediately it will cause various female diseases. One complementary treatment that is believed to be able to reduce the symptoms of vaginal discharge is using boiled water from red betel leaves (piper crocatum) (Firmanila et al., 2016). This study aims to evaluate the effect of giving boiled red betel leaves on vaginal discharge in adolescents. The research design took the form of a quasi-experiment with a two-group pre-post test design. Sampling used purposive sampling technique with a total of 64 people. The results of the study in the case group were 23 people (71.9%) with light scale vaginal discharge and 9 people (28.1%) with moderate scale, 31 people (69.9%) in the control group medium scale and 1 person (3, 1%) on the weight scale. Statistical test results p-value = 0.000 (case) and 0.005 (control) where p-value < 0.05, meaning there is an effect of red betel leaves on reducing vaginal discharge. Teenagers with vaginal discharge can use boiled water from red betel leaves as a treatment.